- KATEGORI FEATURE DALAM PEMBERITAAN TATKALA.CO: - - Desiani, Ni Kadek (Wacana : Majalah Ilmiah Tentang Bahasa, Sastra Dan Pembelajarannya, 2024)
The mass media or what is called journalistic media is one of the aspects that has received very large influence because of the development of electronic media. It is because the news can be disseminated very easily. This makes journalists race to modify the writing format so that it can be more attractive to readers. One of the new journalism variants chosen by journalists is feature. Journalistic article writing that uses feature writing types can be found on the electronic mass media website Tatkala.co. Unlike straight news content which emphasizes the 5W+1H elements with the inverted pyramid rule, features emphasize the "How" and "Why" elements with processes, details of events, and background. The research method used is descriptive qualitative method and data collection techniques used are interviews and literature or documentation studies. Based on the analysis, the feature categories found in the Tatkala.co news are profile features, historical features, adventures features, seasonal event features, human experience features, lifestyle features. Keywords: journalism, features, electronic media